Third-Party Intervention in Wild Western Lowland Gorillas (Gorilla gorilla gorilla) - Stephan, Claudia (International Journal of Primatology, 2019)
The evolution of cooperation is one of the most interesting conundrums in comparative primatology. Prosocial behavior, which describes any behavior that increases the well-being of another individual, is a promising candidate for an animal precursor to complex human cooperation (Cronin 2012). Empirical evidence for prosociality in the primate lineage is abundant, e.g., for chimpanzees (Pan troglodytes), bonobos (Pan paniscus), and common marmosets (Callithrix jacchus), but often inconsistent. There are, however, commonly shared features of prosocial behavior: the major evolutionary driving forces seem to be kinship and reciprocity, and acting prosocially typically comes at low fitness costs for helpers. Experimental studies investigating prosocial traits in gorillas (Gorilla ssp.) found that individuals did not consistently benefit others, even if doing so would have presented no costs for themselves. In contrast, observational studies in captivity and the field have reported that gorillas form coalitions against lower-ranking or out-group individuals (Rosenbaum et al. 2016; Scott and Lockard 2007), and that they consolidate and reconcile after conflicts (Cordoni et al. 2006). Individuals still helped only when the risk of physical harm to the helper was low or the inclusive fitness benefits were high because they helped closely related individuals or individuals that were likely and physically able to return the favor. It remains unclear whether gorillas also support each other in situations that pose greater risks to the helper’s fitness, such as providing support against physically stronger or more dominant opponents, or in favor of unrelated individuals. Here I report a third-party intervention in wild western lowland gorillas (Gorilla gorilla gorilla), performed by a black-back male against a young silverback that attacked a juvenile that is most likely unrelated to the intervening black-bac